Operation Toba in Northeast Argentina: the spread of the State of Terror (1975–1977) - Jussaramar da Silva (Ибероамериканские тетради, 2023)
The purpose of this article is to demonstrate how Argentine experience of internal repression was passed on to Paraguay as a result of the meetings between its intelligence services. The meetings were carried out by the military in the 1970s, aiming at joint operations of political persecution and extermination of the opponents of the dictatorships that prevailed in these two countries. The author analyzes documentation transmitted during the meeting called IIda Regional Bilateral Meeting of Intelligence between Paraguay and Argentina in 1978. Documentation reports to the Paraguayan military the strategies and tactics of war developed by the Argentine armed forces in the so-called Operation Toba. The importance of discussing Operation Toba is to demonstrate the similarity of the repressions that took place in other countries of the Southern Cone. The techniques and tactics used illustrate that such massacres have repressive synchrony and are consistent with a single internationalized process of repression. Although the repression called Operation Toba was developed only by the Argentine State, it demonstrates an international chain of repression, as well as the similarity in the modus operandi of the precepts of the widespread Counter-Revolutionary War Doctrine, developed by the French during the fighting in Indochina and Algeria in the 1950s.